Dyskurs diet odchudzających we współczesnej włoskiej prasie kobiecej. Analiza jakościowa - Ozimska, Joanna (Scripta Neophilologica Posnaniensia, 2021)
The discourse of slimming diets in contemporary Italian women's press. Qualitative analysis. Based on a corpus of articles extracted from contemporary Italian female magazines (2021) Donna Moderna and Grazia, this paper examines the nature of discourse of slimming diet. It is shown that the discourse has changed compared to the study conducted on the material from 2005-2008. Altogether 29 monthly issues have been analyzed. Currently emerging corpus does not contain many persuasive techniques related to emotions (Aristotle's pathos), the credibility of provided advice is enhanced mostly by arguments from authority (ethos). The innovation thus lies in the references to currently important societal topics, such as ecology (a manifestation of linguistic fashion). The research based on a rhetorical tools and analysis of press discourse shows that the topic of weight loss is treated nowadays with greater awareness and is being transferred to the pages of the men's press, in women's magazines its place is taken by e.g., cosmetic-surgical, or ecologic discourse. The conclusions from own research have been preceded by a review of theoretical issues in the field of a modern concept of a slimming diet, myth of beauty, development of the press in Italy, the role of cuisine and food in the Italian women's press.